The use of public resources by women candidates in Ecuador - Bolaños Moreno, Mónica Estefanía (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2024)
This research work refers to the central role played by women in society; and in particular, the female candidate will be addressed. In this context, it should be noted that Ecuador, like any other country, has its own way of governing, derived from its political, economic, and cultural history. This work mainly does a bibliographic survey that accounts for the trends, strengths, and challenges faced by women candidates; and, the role of money as a key element of politics and elections. Reading this work becomes enriching for those who want to approach the study of the political and participatory culture of women, which in turn will allow this article to be much closer to the Ecuadorian reality.
Keywords: women; candidates; politics; money; elections